Pregnancy Outcomes of Teenage Mothers at Klaeng Hospital - Techapalokun, Somnuk (Journal of Health Science of Thailand, 2017)
The objective of this retrospective descriptive study was to assess the obstetric outcomes of teenage mothers who delivered at Klaeng hospital during February, 2007 - January, 2008. The study group consisted of 320 teenage mothers aged 13-19 years. The result showed that the mean age was 17.6 years. About 77.5 percent of teenage mothers had been attended to at the antenatal care unit at least four times. The normal delivery rate was 73.1 percent. The most frequent obstetric complications was cephalo-pelvic disproportion (9.1%) and premature labour (8.8%). Low birth weight less than 2,500 grams was 10.9 percent. The conclusion is that the common complications and outcomes in teenage mothers are cephalo-pelvic disproportion, premature labour and low birth weight. Therefore, the teenage mother should be included in the high risk group to prevent these complications and negative outcomes.